Electrocarboxylation: towards sustainable and efficient synthesis of valuable carboxylic acids - Matthessen, Roman; Fransaer, Jan; Binnemans, Koen; De Vos, Dirk E (Beilstein journal of organic chemistry, 2014)
The near-unlimited availability of CO 2 has stimulated a growing research effort in creating value-added products from this greenhouse gas. This paper presents the trends on the most important methods used in the electrochemical synthesis of carboxylic acids from carbon dioxide. An overview is given of different substrate groups which form carboxylic acids upon CO 2 fixation, including mechanistic considerations. While most work focuses on the electrocarboxylation of substrates with sacrificial anodes, this review considers the possibilities and challenges of implementing other synthetic methodologies. In view of potential industrial application, the choice of reactor setup, electrode type and reaction pathway has a large influence on the sustainability and efficiency of the process.